LEGAL PROTECTION FOR PATIENTS IN THE IMPLEMENTATION OF HEALTH SERVICES AT CLINICS IN DUMAI CITY - Juwita Yanti Pakpahan; Novi Juli Rosani Zulkarnain (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study analyzes the legal protection of patients in health services provided by clinics in Dumai City under Indonesia’s current health-law framework. The research uses a normative juridical method with statutory and conceptual approaches. Primary legal materials include the 1945 Constitution, Law Number 17 of 2023 on Health, Government Regulation Number 28 of 2024, Minister of Health Regulation Number 11 of 2025, and related rules on medical records, referrals, pharmaceutical services, and personal data protection. The study finds that patient protection operates through preventive and repressive mechanisms. Preventive protection requires lawful clinic licensing, professional competence, service standards, informed consent, confidentiality, accurate medical records, patient safety, transparent fees, and effective referral procedures. Repressive protection is available through internal complaints, professional and administrative examination, mediation, civil claims, and criminal proceedings where legal elements are fulfilled. The main implementation challenge is not the absence of norms, but inconsistent documentation, insufficient communication, weak complaint management, and limited supervision. Therefore, clinics and the Dumai City Government should strengthen standard operating procedures, patient information systems, incident reporting, periodic compliance audits, and accessible non-litigation dispute resolution.